P1741 Echocardiographic assessment of rate versus rhythm control strategy in patients with persistent atrial fibrillation. (17th January 2020) - Piatkowski, R; Kosior, D A; Kochanowski, J; Szulc, M
Abstract: BACKGROUND: Patients with persistent atrial fibrillation (AF) can be managed with either rhythm or rate control strategy. The restoration and maintenance of the sinus rhythm (SR) is not superior to the rate control regarding the total mortality and the rate of thromboembolic complications. Data concerning the effect of these strategies on left ventricular morphology and function is missing. PURPOSE: The objective of our prospective randomised multicenter study in patients with persistent AF was to evaluate the effect of these two approaches on left ventricular morphology and function. METHODS: The study group consisted of 205 patients (F/M 71/134; mean age 60.8 ± 11.2 years), including 101 patients randomized to the rate control approach (Group I) and 104 patients randomized to SR restoration with cardioversion and subsequent antiarrhythmic drug treatment (Group II). Mean duration of AF was 231.8 ± 112.4 days. At the end of follow-up (12 months), SR was present in 64% of patients in Group II. Echocardiographic examination was performed at a baseline and at 2 and 12 months. In the rate-control group, both right (22.1 ± 4.1 vs. 23.2 ± 3.8 cm2; p < 0.05) and left atrial (25.9 ± 5.2 vs. 26.8 ± 4.6 cm2 p < 0.05) enlargement was observed during the 12 months follow-up. A significant decrease in right (21.8 ± 3.0 vs. 21.2 ± 3.5 cm2; p < 0.05) and left atrial (26.2 ± 4.6 vs. 25.5 ± 5.0 cm2; p < 0.05) size in the rhythm control arm was observed. Both strategies led to a significant increase in left ventricular fractional shortening (32.1 ± 7.3 vs. 34.2 ± 6.5% and 31.3 ± 6.7 vs. 35.5 ± 8.9%, respectively; p < 0.05). The comparison of the left ventricular end-diastolic diameter revealed no difference within and between groups (50.8 ± 5.6 mm vs. 52.2 mm ± 6.8 mm at a baseline and 50.0 ± 6.0 vs. 52.0 ± ± 7.4 mm at 12 months, respectively). In rhythm-control group such trend was observed only in pts. with successfully maintained SR. According to LV function improvement, rhythm-control strategy was preferred in pts. with hypertension (RR 2.63; 95% C.I.: 0.93-5.45; p < 0.05) or congestive heart failure in NYHA II or III class (RR 2.13; 95% C.I.: 0.98-4.42; p < 0.05). CONCLUSIONS: Both strategies led to a significant increase in LV FS. Rate-control strategy led to right and left atrium enlargement, but rhythm control resulted in their decrease.